Technique differences among male and female intermediate hurdlers and steeplechasers - Bollschweiler, L.; Hunter, I.; Feland, J. B.; Hopkins, J. T. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
In the sport of track and field, proper hurdling technique is a complicated combination of various running and jumping kinematics. With most research having been done on sprint hurdling, there is a need for further research on hurdling events of different distances. The intermediate hurdles (IH) and the steeplechase (SC) are two events where there are a number of differences in hurdling technique. This study compared the differences in hurdling technique between events (IH and SC) as well as the differences in technique between genders.